Analyzing Contractor Business Strategies Using Environmental Factors Analysis Summary (EFAS) and Internal Factors Analysis Summary (IFAS): A Case Study of Citacipta Project - Mubarok, Ramdhan Faizal; Hendrayati, Heny; Sultan, Mokh Adib (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze contractor business strategies using the Environmental Factors Analysis Summary (EFAS) and Internal Factors Analysis Summary (IFAS) approaches. A case study was conducted on Citacipta Project, a construction sector contractor. Data were collected through surveys and in-depth interviews with the company's management to understand the external and internal factors influencing organizational performance. The analysis results indicate that the EFAS and IFAS approaches effectively identify strategic factors impacting the company's performance. EFAS facilitates the categorization and evaluation of opportunities and threats from the external environment, while IFAS enables the company to analyze its internal strengths and weaknesses. By leveraging both analyses, Citacipta Project can formulate adaptive strategies to address the challenges of a dynamic market. Overall, this research provides insights into how an integrated approach can be applied by contractors to enhance competitiveness amidst the increasingly complex construction industry. These findings contribute to the development of more adaptive business strategies within the construction sector.